2018
DOI: 10.12669/pjms.345.15083
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Neuro-Cognitive Assessment Battery for Stroke Patients (NCABS) in Pakistan

Abstract: Background & Objective:Post Stroke Cognitive Impairments (PSCI) occur frequently in stroke survivors resulting in devastating consequences affecting daily living of survivors. Currently, there exists scarcity of sound assessment tools for the evaluation of PSCI as most of the commonly used scales offer a number of clinical (requires motor and linguistic skills) and cultural limitations (requires academic exposure). Therefore, current study was aimed at evaluating the efficacy of Neuro-Cognitive Assessment Batt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The Neurocognitive Assessment Battery for stroke patients (N-CABS) was developed and validated locally to measure Post Stroke Cognitive Impairment (PSCI). 10 It was utilized in this study to assess the degree of impairment among the sample. The battery consists of nine sub-tests that include orientation, attention span, paired associate learning test, naming, similarities, arithmetic, Bell's test, block design and non-verbal learning test.…”
Section: Methodsmentioning
confidence: 99%
“…The Neurocognitive Assessment Battery for stroke patients (N-CABS) was developed and validated locally to measure Post Stroke Cognitive Impairment (PSCI). 10 It was utilized in this study to assess the degree of impairment among the sample. The battery consists of nine sub-tests that include orientation, attention span, paired associate learning test, naming, similarities, arithmetic, Bell's test, block design and non-verbal learning test.…”
Section: Methodsmentioning
confidence: 99%
“…Some previous studies suggested that a high level of social support was related to the improvement of diabetes. Another study found that having high social support prompted controlling their diabetes effectively 13 . social sports positive effect on glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…9 Sufficient literatures is available on various questionnaire development and validation studies in fields of Allied Health Professionals in Pakistan. [10][11][12] but limited literature for receptive and expressive language assessments tools that can help in diagnosis of language disorders.…”
Section: Introductionmentioning
confidence: 99%